1991
DOI: 10.1044/jshr.3406.1423
|View full text |Cite
|
Sign up to set email alerts
|

Consonant Lingual-Palatal Contacts Produced by Normal-Hearing and Hearing-Impaired Children

Abstract: Ten normal hearing (NH) and 18 profoundly hearing-impaired (HI) children were recorded using palatometry and audiotape while producing the consonants /t,d,k,g,s,z,∫/ in CV syllables (V=/i, α/). The lingual-palatal contacts produced by the NH subjects for the alveolar stops were undifferentiated across voicing and vowel environment differences. Lingual-palatal contact patterns for the velar stops differed for vowel environment but not for voicing. The /s/ and /z/ sibilants were distinguished by groove width but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 16 publications
4
27
1
Order By: Relevance
“…The findings agree with previous EPG studies reporting deviant production of sibilants, velar stops, and liquids (e.g. Dagenais and Critz-Crosby, 1991;Fletcher et al, 1991;Dagenais et al, 1994;Crawford, 1995). Bernhardt et al (2003, p. 203) noted that sibilants and liquids were the 'least well-established' consonant categories across the adolescent speakers of their study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings agree with previous EPG studies reporting deviant production of sibilants, velar stops, and liquids (e.g. Dagenais and Critz-Crosby, 1991;Fletcher et al, 1991;Dagenais et al, 1994;Crawford, 1995). Bernhardt et al (2003, p. 203) noted that sibilants and liquids were the 'least well-established' consonant categories across the adolescent speakers of their study.…”
Section: Discussionsupporting
confidence: 92%
“…More recently, important insights into the articulatory characteristics of consonantal segments have been gained by the use of experimental techniques such as electropalatography (EPG). Dagenais and Critz-Crosby (1991) provided a description and categorization of gestures occurring during obstruent production in the speech of unintelligible 10-15-year-old children with hearing impairment. They reported a higher frequency of open gestures during the production of alveolar and velar obstruents and of grooved gestures during postalveolar fricatives.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the EPG patterns recorded from older school age children are similar to younger children, but older children have somewhat less contact overall (Dagenais and Critz-Crosby, 1991;Fletcher, 1989). In addition, the hard palates of cleft speakers (at least those who have a cleft of the alveolus) tend to be smaller, narrower, and more irregular in shape than those of normal speakers.…”
Section: Discussionmentioning
confidence: 95%
“…A number of previous EPG studies of normal adult speakers' productions of alveolar stops have shown that /t/, /d/ and /n/ do in fact have similar "horseshoe" shaped configurations (Dagenais, Lorendo and McCutcheon, 1994;Goozée, Murdoch and Theodoros, 1999;Hardcastle and Gibbon, 1997;McLeod and Roberts, 2005;McLeod, 2006;McAuliffe, Ward and Murdoch, 2001;Stone and Lundberg, 1994). EPG studies show that normal speakers (adults and children) produce this horseshoe configuration by a combination of lateral bracing and an upward movement of the tongue tip/blade to the alveolar ridge (Dagenais and Critz-Crosby, 1991;Fletcher, 1989). An important additional feature is that speakers need to "tense the lateral borders of the tongue to produce a spoonshaped configuration" (Fletcher, 1992, p. 99).…”
Section: Introductionmentioning
confidence: 99%
“…Two children (aged 10 and 12 years) with normal vocal tract structure and typical speech development provided a limited amount of normative data. Additional normative data were available in previously published studies (Dagenais and Critz-Crosby, 1991;Fletcher, 1989), which reported data from 19 typically developing children aged 6-14 years.…”
Section: Participantsmentioning
confidence: 98%